We three - Harwood-Jones, Markus, 1991- (RealLove., 2019)
"Having the courage to love beyond established lines. Jasbina "Jassie" Dhillon is at summer performance camp to address concerns of her parents and teachers over her struggles at school and her lack of close friends. To Jasbina's surprise, she quickly makes two new friends, Ams and Sydney. The problem is that the pair can't seem to stand each other, and Jassie realizes she's got romantic feelings for both of them. Just as Jassie is worried she may need to choose one over the other, Ams and Syd start to get along -- but a little bit too well. It seems like Jassie may have missed her chance at both love and friendship, since Ams and Syd only seem to have eyes for each other. Jassie is upset until Ams and Syd tell Jassie they want to be with her too. The three spend their time at camp working out their relationship in the face of the misunderstandings, assumptions and envy of counsellors and fellow campers alike. As camp gets close to ending, Syd proposes that the three of them run away from camp together. Ams feels the only solution is for the three of them to just end their relationship. Jassie, heartbroken and hurt, realizes she needs to find the courage to convince her partners that their love can survive in the real world."--